2016
DOI: 10.1016/j.mimet.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of long term frozen storage of faecal samples on protein concentration and protease activity

Abstract: BackgroundThe proteome is the second axis of the microbiome:host interactome and proteases are a significant aspect in this interaction. They interact with a large variety of host proteins and structures and in many situations are implicated in pathogenesis. Furthermore faecal samples are commonly collected and stored frozen so they can be analysed at a later date. So we were interested to know whether long term storage affected the integrity of proteases and total protein and whether historical native faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…We aimed here simply to evaluate the effect of the long-term storage of stool samples destined for processing for 16S rRNA gene sequencing, but our findings suggest that long-term storage may influence samples stored for metagenomics, particularly for studies at higher levels of resolution (e.g. at strain level), transcriptomic, metabolomic or proteomic studies 33,43 . Depending on the final use, methods of sample collection and preservation other than those described here may be used, with potentially different impacts on microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed here simply to evaluate the effect of the long-term storage of stool samples destined for processing for 16S rRNA gene sequencing, but our findings suggest that long-term storage may influence samples stored for metagenomics, particularly for studies at higher levels of resolution (e.g. at strain level), transcriptomic, metabolomic or proteomic studies 33,43 . Depending on the final use, methods of sample collection and preservation other than those described here may be used, with potentially different impacts on microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…Bile salt hydrolase activity assay. Faecal water was prepared and total faecal protein quantified similarly to a method previously-described 41 , but with the addition of bacterial and mammalian protease inhibitor cocktails (G Biosciences, Uttar Pradesh, India), as well as Dithiothreitol to 1 mM final concentration (Roche, Basel, Switzerland) (to minimise enzyme oxidation 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the stability of long term frozen storage of fecal M2-PK needs evaluation. A previous study evaluating protein degradation in fecal samples stored intact (rather than as extracted proteins) showed that proteins remained stable in samples frozen at both − 20 and − 80 degrees Celsius after 24 h, 1 week, 1 month, 3 months, 6 months and 1 year [34]. There was a significant difference in age between CF and HC subjects at sample collection, however it was demonstrated that fecal M2-PK levels were independent of age using linear mixed model analysis.…”
Section: Mutationmentioning
confidence: 96%